External supravesical hernia is a rare type of abdominal wall hernia: A case report - Saha, Pankaj Kumar; Roy, Ratna Rani; Khan, Mohammad Emrul Hasan; Rahman, Md Mamunur; Alam, Kazi Shafiqul; Rabbani, Md Golam (Journal of Shaheed Suhrawardy Medical College, 2017)
The first case of external supravesical hernia was made in 1804; but it is so rare that it is very difficult to find any case reported in Bangladesh. Here a case of external supravesical hernia is described in a male who was presented with a left sided direct incomplete reducible inguinal hernia. This report aims to review and discuss the surgical anatomy of these rare supravesical hernias and calls attention to the confusing presentation and treatment of this condition J Shaheed Suhrawardy Med Coll, 2015; 7(1):40-41